Antifouling and antibacterial performance evaluation of polyethersulfone membranes modified with AZ63 alloy - Yasin Ozay; Aya Alterkaoui; Kürsat Kahya; Sadin Özdemir; Serpil Gonca; Nadir Dizge; Kasım Ocakoglu; Mustafa Kemal Kulekci (Water Science and Technology, 2023)
Antibacterial membranes have attracted researchers’ interest in recent years as a possible approach for dealing with biofouling on the membrane surface. This research aims to see if blending AZ63 Mg alloy into a polyethersulphone (PES) membrane can improve antifouling and separation properties. The composite membranes’ pure water flux continued to increase from pristine PES to PES/AZ63 2.00 wt%. The results showed that PES/AZ63 2.00 wt% membrane supplied the highest permeate flux of E. coli. The steady-state fluxes of AZ63 composite membranes were 113.24, 104.38 and 44.79 L/m2h for PES/AZ63 2.00 wt%, 1.00 wt%, and 0.50 wt%, respectively. The enhanced biological activity of AZ63 was studied based on antioxidant activity, DNA cleavage, antimicrobial, anti-biofilm, bacterial viability inhibition and photodynamic antimicrobial therapy studies. The maximum DPPH scavenging activity was determined as 81.25% with AZ63. AZ63 indicated good chemical nuclease activity and also showed moderate antimicrobial activity against studied strains. The highest biofilm inhibition of AZ63 was 83.25% and 71.63% towards P. aeruginosa and S. aureus, respectively. The cell viability inhibition activity of AZ63 was found as 96.34% against E. coli. The photodynamic antimicrobial therapy results displayed that AZ63 demonstrated 100% bacterial inhibition when using E. coli. HIGHLIGHTS AZ63 Mg alloy was blended to polyethersulphone (PES) membrane.; Biologic activity of AZ63 was studied based on antioxidant activity, DNA cleavage, antimicrobial, anti-biofilm, bacterial viability inhibition and photodynamic antimicrobial therapy studies.;